Hydatic liver cyst fistulized in the duodenum: A case report - Touarhi, Hamza; Marzouki, Wiem; Mseddi, Mohamed Ali; Zahaf, Bechir; Sassi, Karim; Ben Slima, Mohamed (Biomedicine & Healthcare Research, 2025)
Background: Hydatic cyst is a zoonosis that is endemic in developing countries. The most frequent complication of a hydatic liver cyst is communication with the biliary tract. Communication with the duodenum is an uncommon complication. Case presentation: A 60-year-old woman presented with abdominal pain and vomiting. There was no jaundice or fever. A biological inflammatory syndrome was identified. An abdominal computed tomography (CT) scan revealed a fistula between a centro-hepatic hydatid cyst and the first portion of the duodenum. The subject underwent disconnection of the fistula and a pericystectomy, followed by placement of a tube duodenostomy for the fistula and a subhepatic drain. The postoperative period was uneventful. Conclusion: Despite the benign nature of hydatic cysts, duodenal fistula is a unusual complication. Surgical treatment is determined by the size of the duodenal defect.